Visualization of granzyme B‐expressing CD8 T cells during primary and secondary immune responses to Listeria monocytogenes. Issue 1 (May 2015) - Mouchacca, Pierre; Chasson, Lionel; Frick, Melissa; Foray, Chloé; Schmitt‐Verhulst, Anne‐Marie; Boyer, Claude
Summary CD8 T cells contribute to long‐term protection against Listeria monocytogenes infection by differentiating into memory T cells. These rapidly respond to antigen or inflammation upon secondary infection. In this study we used CD8 T cells from OT1 mice and CD4 T cells from OT2 mice expressing a fluorescent chimeric granzyme (GZMB‐Tom) protein to monitor the primary response to infection with ovalbumin‐expressing L. monocytogenes (Lm‐OVA). We show that, unlike poorly responding CD4 T cells, CD8 T cells readily proliferated and expressed high levels of GZMB‐Tom as early as 2 days after infection. FACS analysis showed GZMB‐Tom expression in undivided CD8 T cells, with its level increasing over one to four divisions. OT1 T cells were visualized in the T‐cell zone by confocal microscopy. This showed GZMB‐Tom‐containing granules oriented towards MHCII‐positive cells. Twenty hours later, most OT1 T cells had divided but their level of GZMB‐Tom expression was reduced. Recently divided OT1 cells failed to express GZMB‐Tom. Fourteen hours after secondary infection, GZMB‐Tom was re‐expressed in memory OT1 T cells responding either to Lm‐OVA or L. monocytogenes. Differences in the activation phenotype and in the splenic distribution of OT1 T cells were observed, depending on the challenge. Notably, OTI T cells with polarized granules were only observed after challenge with cognate antigen. This work showed that the GZMB‐Tom knock‐in mice in which GZMB‐Tom faithfully reproduced GZMB expression, provide useful tools to dissect mechanisms leading to the development of anti‐bacterial effector and memory CD8 T cells and reactivation of the memory response to cognate antigen or inflammatory signals.